Resistência flexural e estabilidade cristalina de uma zircônia translúcida monolítica submetida a desgaste, polimento e desafios térmicos - Souza, Raisa Hintz de (2019)
The aims of this thesis were: i) evaluate the effects of different grinding and polishing methods (diamond burs and polishing and finishing points) on the surface micromorphology (roughness and topography), biaxial flexural strength, and phase transformation of a yttria-stabilized tetragonal zirconia polycrystal (Y-TZP); and ii) evaluate the influence of two distinct aging methods (autoclave and thermocycling) on the surface micromorphology (roughness and topography), biaxial flexural strength, and phase transformation of a yttria-stabilized tetragonal zirconia polycrystal. Ninety Y-TZP discs (Vipi Block Zirconn) were prepared, which, after sintering, measured 12 mm in diameter and 1 mm in thickness. The specimens were divided into nine groups (n = 10), according to the surface treatment: as sintered (no surface treatment), grind (diamond bur), grind + polish (diamond bur followed by polishing points); and according to the aging method (low temperature degradation – LTD): autoclave (134°C, 2.2 kgf/cm2 , 5h) and thermocycling (200.000 cycles of 5 and 55oC). The average roughness (Ra) was measured by using a contact roughness meter. The biaxial flexural strength was measured in an universal testing machine, with a loading speed of 1 mm/min, using the piston on three balls method, with the specimens immersed in artificial saliva. The quantification of the monoclinic-zirconia phase fraction was obtained based on X-ray diffraction spectra (XRD). Results were statistically analyzed by two-way ANOVA and Tukey test (α = 0,05). The correlation between roughness and biaxial flexural strength was analyzed by Spearman correlation coefficient. With regards to surface treatment, grind resulted in an increase in roughness and flexural strength compared to the group as sintered, while grind + polish yielded intermediate roughness and flexural strength similar to the group grind. Aging had little effect on roughness, yet it yielded a significant reduction in strength. Phase transformation from tetragonal to monoclinic was observed in all groups, caused by either mechanical stresses (grind and polish) or by LTD. The use of diamond burs to grind zirconia surface may result in deleterious effects on the surface quality of monolithic zirconia restorations, yet has a potential toughening effect by phase transformation. However, when zirconia is exposed to LTD, regardless of the surface treatment, degradation of the surface quality and strength are observed.